Expert-Analytical Platform as the Development of a Modern Standard of Work in Science and Business - M. Yu. Karpushin; A. A. Suslova; A. V. Stoupakova; A. A. Korshunov; A. Yu. Bezzubov; N. V. Beletskaya; R. S. Sautkin; A. P. Antonov; V. V. Chernyavsky; N. R. Galin; E. V. Svirilina; A. P. Zavyalova; et al. (Georesursy, 2025)
Modern challenges and speed of information exchange for decision-making require new tools capable of storing and processing large amounts of data. The paper describes the principles, relevance and foundations of the expert-analytical platform MyGeoMap. The platform is designed to optimize and solve a wide range of scientific and practical problems. When creating the platform, we used the experience and knowledge accumulated by the Petroleum Geology Department, Geological Faculty of the Lomonosov Moscow State University. The platform allows to solve the following problems: promptly obtain information about oil and gas facilities anywhere in the world, search for analog deposits, use the platform as a corporate database and / or analytics tool, and much more. To date, the platform has collected more than a million geological, geophysical, industrial, environmental and other objects with georeferencing and attribute information. All data is collected from various open sources and integrated into a single digital environment. Data verification is carried out by qualified employees of the Institute for Advanced Oil and Gas Research of Moscow State University. The platform has its own intellectual developments, including the use of artificial intelligence tools for analytics and building predictive models. Platform users represent a specialized expert community whose potential has yet to be revealed. The MyGeoMap platform is a unique project that already today solves a number of interesting and important problems not only for the search and exploration of oil and gas fields, but also for other areas of economic development where geology plays a key role.